Minimalisasi Penurunan Kadar Beta-Karoten dan Protein dalam Proses Produksi Tepung Ubi Kayu - Ahmad Fathoni; N. Sri Hartati; Nur Kartika Indah Mayasti (Perum BULOG, 2016)
The conventional method of cassava flour production significantly reduces the levels of beta-carotene and protein in the product. Therefore, the method needs to be improved in order to minimize the loss. This study investigated the effect of some treatments on beta-carotene and protein stability including the use of a) various antioxidant agents; 0.3 percent of ascorbic acid, 0,3 percent of sodium metabisulphite and 8 percent of mixture of gum arabic and dextrin (1 : 1), b) different drying methods; cabinet dryer at 40°C and 50°C and sun drying, in cassava flour processing of two carotenoid-rich local cassava varieties; Adira 1 and Mentega 2. The results showed that the use of sodium metabisulphite and cabinet dryer at 40°C were the most effective methods to minimize the loss of beta-carotene and protein. Beta-carotene and protein content in cassava flour obtained from those treatments were 9,44±0,10 µg/g and 2,41 percent compared to control which was 4,92±0,29 µg/g and 2,1 percent whereas sun drying method reduced beta-carotene and protein content by 55,82 percent and 18,43 percent, respectively. Packaging in aluminum bags minimized the loss of beta-carotene and protein in the product during the first 3 months of storage.